Doing Well by Blowing Right: How Whistleblowing Practice Enhances Corporate Risk Disclosure - Dewi Mustika Ratu (JURNAL AKUNTANSI DAN AUDITING, 2025)
Given the prevalence of corruption scandals in State-Owned Enterprises (SOEs), it is crucial to assess the effectiveness of whistleblowing systems in promoting transparency of risk management information. Therefore, this study investigates the relationship between whistleblowing practices and the level of corporate risk disclosure. Using archival methods, observations were conducted between 2016 and 2021 at SOEs listed on the Indonesia Stock Exchange (IDX). As expected, using stakeholder theory and the "doing well by doing good" perspective, effective whistleblowing provides information about current and potential risks that are not easily detected. Therefore, regulators and investors need to critically evaluate information in risk disclosures, by considering whistleblowing as a positive signal of reliable corporate governance.